Build Online Booking Application Firstudio Music Based On Crowdsourcing - Firmanto, Rendy Destara; Wulandari, Sri Hariani Eko; Ningsih, Norma (Jurnal Sistem Informasi Universitas Dinamika (JSIKA), 2018)
Currently many music studios are still using manual ordering in every process of their business, may be practically almost all the studios that exist in Indonesia are still using the manual way, therefore many people are still had difficult way in ordering because the schedule always crashes with the other studio users, Moreover they have to consider the mileage and then they survey the place, studio situations, rooms, tools and prices. Another problem is certainly felt by the studio owner who sometimes confused how to promote their music studio to be known by many people and is not less competitive with other music studios. You can see from the problems above, then we need an application that can bridge between studio owners and users of music studios. So the solution offered is to design an online booking application based Firstudio music crowdsourcing. With the application of Firstudio certainly can help the users of music studios in terms of booking music studio online quickly and accurately. Not only studio users, but studio owners will also benefit, they can promote their music studio on this website, moreover the absence of fees for their studio advertisements.